INCIDENCE, DEPTH, AND SEVERITY OF POVERTY AMONG RURAL AND PERI-URBAN FARMING HOUSEHOLDS OF KWARA STATE, NIGERIA- A META ANALYSIS - Kamoru Bello; Amos omofaiye; Ezekiel Ojediran (American Journals Publishing, 2022)
The worrying increase in peri-urban population and the decreasing rural farming population necessitated an inquiry into poverty indices of the communities. The usefulness of dependable information on the rural and peri-urban farming populace must be underscored. The study examined the poverty levels of the rural and peri-urban households. Samples were selected through the use of a four-stage random sampling approach.Cross-sectional data from the one-hundred and twenty farming households sampled were collected using a structured interview schedule administered on the households in a round-table format. Data were analyzed using the FGT measures, Sen and Watts index on the mean, medial and modal income of the households. Results show that in terms of poverty depth, severity, Sen index, and Watts index, peri-urban farming households fared better than rural farming households. It is therefore recommended that farming households be discouraged from migrating to peri-urban (and urban) areas at the expense of agriculture and that farming be made more favourable in the rural areas.
Keywords: Farming households; peri-urban; poverty indices